Effect Pengaruh Pemberian Tepung Kunyit Dalam Ransum Yang Mengandung Bawang Hitam Terhadap Retensi Lemak Kasar Ayam Broiler: Pengaruh Pemberian Tepung Kunyit Dalam Ransum Yang Mengandung Bawang Hitam Terhadap Retensi Lemak Kasar Ayam Broiler - Hasan, M. Aqmal Aprilla; Marpaung, Rifqi Nadela; Nurhayati, Nurhayati; Nelwida, Nelwida; Berliana, Berliana (Fakultas Peternakan Universitas Jambi, 2024)
Background: The nutritional quality of animal feed is the most important factor when using and selecting animal feed ingredients. One of the determinants of the quality of feed ingredients or rations is looking at the retention of feed substances, namely how much feed substances are retained in the digestive tract, efforts to improve and optimize the retention of feed substances by adding feed additive such as turmeric flour and black garlic. Purpose: This study aims to see how turmeric flour is used in rations containing black garlic on crude fat retention in broiler chickens. Methods: This study used 200 DOC of broiler chickens strain MB 202 and was designed by a completely randomized design (CRD) with 5 treatments and 4 replicates. The treatments consisted of P0 = 100% commercial ration (control), P1 = P0 + 3% black garlic, P2 = P1 + 0.5% turmeric flour, P3 = P1 + 1% turmeric flour, P4 = P1 + 1.5% turmeric flour. The variables observed in this study were dry matter retention, organic matter retention, and crude fat retention. Data were processed using analysis of variance and Duncan's multiple range test followed the significant effect. Results: The results showed that the use of turmeric flour in rations containing black garlic had a significant increase (P<0.05) in dry matter consumption and organic matter consumption but had no significant effect (P>0.05) on excretion and retention of dry matter, organic matter, and crude fat. Conclusion: From the results of this study it can be concluded that the use of turmeric flour up to 1.5% in rations containing 3% black garlic can be used without any adverse effect on the retention of crude fat in the digestive tract.